Defining duodenitis: quantitative histological study of mucosal responses and their correlations. Issue 10 (October 1985) - Jenkins, D; Goodall, A; Gillet, F R; Scott, B B
Abstract : Biopsies from 56 patients with endoscopically normal duodenal bulbs, duodenitis, or duodenal ulceration were studied for counts of plasma cells, polymorphs, and eosinophils and extent of gastric metaplasia, villous atrophy, and mucosal oedema. A correlation matrix showed that the counts of different types of plasma cells were closely correlated with each other and that there was also a close correlation between the presence of intraepithelial polymorphs, villous atrophy, and gastric metaplasia. Cluster and discriminant analysis indicated that the histological changes could be grouped by their statistical association into three simple categories: normal, which includes many cases incorrectly labelled in some classification systems as mild or chronic duodenitis; histologically defined mild duodenitis, characterised by an appreciable plasma cell response and oedema usually with intraepithelial polymorph infiltration and gastric metaplasia; and severe duodenitis, with an appreciable polymorph response and villous atrophy but decreased plasma cells. Decreased plasma cells may be an important indication of peptic ulceration.